An Improved Integrated Scheduling Algorithm with Process Sequence Time-Selective Strategy. (9th March 2021) - Wang, Zhen; Zhang, Xiaohuan; Peng, Gang
Abstract : The integrated scheduling algorithm of process sequence time-selective strategy (ISAOPSTSS) is an advanced algorithm in the field of integrated scheduling. The proposed algorithm points out the shortcomings of the process sequence time-selective strategy. Generally, there are too many "trial scheduling" times. The authors propose that there is no need to make "trial scheduling" at every "quasi-scheduling time point." In fact, the process scheduling scheme can be obtained by trial scheduling on some "quasi-scheduling time points." The scheduling result is the same as that of the sequence timing strategy. The proposed algorithm reduces the runtime of scheduling algorithm and improves the performance of the algorithm without reducing the optimization effect.